A study on the design changes affecting the construction project: point of view from contractor perspective - Mohd Harisuddin, Hasnan (2018)
Although many project time delays, cost overruns and quality defects particularly in the construction sector are attributed to design changes, the associated issues have not yet been thoroughly investigated. At this time, problems with design changes are still one of the major problems in construction. In today’s practice, every design made at the early stage has been agreed upon by the parties involved in the construction work but on request of the client and been approved by the consultant, the design of the construction can be changed. The objective of this is to study the change in design affecting the construction project from the contractors’ point of view. Questionnaires survey were distributed to the group of contractors accordingly in order to obtain information and analysis on the subject matter which is by identifying the causes affecting the change in design of construction project. The scopes of this research will cover the area in East Coast of Malaysia. It is focusing on the causes of design change in the engineering practitioners. Data gathering carried out by doing literature review and applying a questionnaire survey through contractors that has been selected and registered under CIDB. An analysis being carried out using SPSS software & Relative Importance Index (RII) has shown a tremendous result in finding the most influential factors affecting the design changes. According to all the data being collected, the entire objectives for this study are archived and there are 37 main causes to the design changes in construction projects which have been identified. They are change in design, current economic situation, error or omission occurred during construction phase, replacement of material and work procedure as well as lack of data and information required for the design. While for the effect of design changes, the respondent choose cost overrun while conducting the project as it cannot be completed in time and they agreed to look for another solution other than changing the design to overcome this design changes problems.